Budesonide and formoterol inhibit inflammatory mediator production by bronchial epithelial cells infected with rhinovirus - Skevaki, C. L.; Christodoulou, I.; Spyridaki, I. S.; Tiniakou, I.; Georgiou, V.; Xepapadaki, P.; Kafetzis, D. A.; Papadopoulos, N. G. (Clin Exp Allergy, 2009)
Rhinoviruses (RVs) are responsible for the majority of acute asthma and chronic obstructive pulmonary disease (COPD) exacerbations. RVs infect the lower airways and induce the production of pro-inflammatory and remodelling-associated mediators. Budesonide (BUD) and formoterol (FORM) synergize in controlling asthma and COPD exacerbations; however, their effects on virus-induced inflammation and remodelling are less known.|We investigated whether BUD and FORM synergize in suppressing RV-induced inflammation and remodelling in the airways.|In vitro models of RV infection of BEAS-2B and primary normal human bronchial epithelial (NHBE) cells were used. We assessed the effects of individual and combined drugs administered post-infection, at a clinically relevant concentration range (10(-6)-10(-10) m), on the production of CCL5, CXCL10, CXCL8, IL-6 and the remodelling-associated VEGF and bFGF, using ELISA and RT-PCR.|BUD effectively suppressed RV-mediated induction of all mediators studied, in a concentration-dependent manner. FORM alone suppressed the production of CXCL8 and bFGF. The combination of BUD and FORM had concentration-dependent, additive or synergistic effects in the suppression of RV-induced CCL5, CXCL8 and CXCL10 in both cell types as well as VEGF in NHBE only. Combination treatment also resulted in an enhanced suppression of RV-induced IL-6, and CCL5 at the mRNA level as compared with BUD or FORM alone.|BUD and FORM suppress RV-induced chemokines and growth factors in bronchial epithelial cells in a concentration-dependent, synergistic or additive manner. These data further support the combined use of BUD and FORM in asthma and COPD and intensification of this therapy during exacerbations.
Keywords: Asthma Bronchi Bronchodilator Agents Budesonide Chemokine CXCL10 Chemokines Drug Synergism Epithelial Cells Ethanolamines Fibroblast Growth Factor 2 Humans Inflammation Inflammation Mediators Intercellular Adhesion Molecule-1 Picornaviridae Infections Pul; Chronic Obstructive Respiratory Mucosa Rhinovirus Vascular Endothelial Growth Factor A